Evaluation and Management of Watercraft-Related Injuries for Acute Care Surgeons: Towards Improving Care and Implementing Effective Public Health Prevention Policies - John D. Ehrhardt, Jr., MD; Kevin Newsome, BS; Snigdha Das, BS; Mark McKenney, MD, MBA, FACS; Adel Elkbuli, MD, MPH (Annals of Surgery Open, 2022)
Boating has exposed humans to elemental hazards for centuries. What was once a lifelong craft and time-honored skillset is now, with modern technology, a popular recreational activity. Boating safety has inherent limitations and has been historically challenging to enforce. These circumstances have given way to a rising number of watercraft-associated injuries and fatalities. This review aims to investigate the diagnosis, work-up, and management of watercraft-related injuries, including blunt mechanisms, propeller wounds, water-force trauma, associated marine infections, and submersion injuries, as well as outline gaps in current public health policy on watercraft injuries, potential interventions, and available solutions. Motorboats and personal watercraft differ in size, power modality, and differential risk for injury. Accidents aboard watercraft often share commonalities with motor vehicles and motorcycles, namely: rapid deceleration, ejection, and collision with humans. The complexity of care is added by the austere environment in which many watercraft accidents occur, as well as the added morbidity of drowning and hypothermia. Wounds can also become infected by marine organisms, which require wound care and antimicrobial therapy specific to the aquatic environment in which the injury occurred. The treatment of these patients can be further exacerbated by the prolonged transportation times due to complicated water rescue. There are many measures that can prevent or abate watercraft injuries, but inconsistent regulations and enforcement may impair the success of these interventions. Further research is needed to identify possible solutions to common causes of watercraft injuries, such as inconsistent lifejacket use and bow riding.